Mean reversion in the Finnish stock market and its effect on risk - Pajala, Otto (My University, 2024)
The debate around the predictability of stock prices has been going on for decades and wealth managers have been scrambling to find any type of long-term edge over the market. This search inspired De Bondt and Thaler (1985) to compare returns between a portfolio of past losers and a portfolio of past winners. They found that past losers tended to have higher than market average returns in the following years. The phenomenon causing this is now known as reversal which has had a profound impact on how we think about the behaviour of stock prices and sparked numerous studies on the topic of mean reversion. The aim of this thesis is to find out whether the Finnish stock market (OMXHPI-index) is mean reverting and if so, how long does it take for stock returns to revert to their mean (50-day moving average) and more importantly, how does this reversal affect risk. The presence of mean reversion is studied using a modified version of Lo and MacKinlay’s (1988) variance ratio and the Hurst exponent and half-life. The risk measures chosen are value at risk and expected shortfall, otherwise known as conditional value at risk. The results show that the Finnish stock market is mean reverting, and it takes 8 to 15 trading days for stock price changes to revert back to their mean. The Hurst exponent and half-life have a low positive correlation with the risk measures. Additionally, they are statistically significant methods of explaining the changes with the risk measures based on the robust standard errors test. This means that as the amount of mean reversion increases, the amount of risk in the market also increases. Changes in half-life had a stronger impact on risk. The findings of this thesis can be valuable for portfolio managers looking to hedge risk or opportunistic investors aiming to outperform the market.

Osakkeiden hinnanmuutoksien ennustettavuudesta on käyty keskustelua jo vuosikymmeniä, ja varainhoitajat pyrkivät löytämään pitkän aikavälin etulyöntiaseman markkinoihin nähden. Tämä innoitti De Bondt ja Thaleria (1985) vertailemaan aiempia häviäjiä sisältävän salkun ja aiempia voittajia sisältävän salkun tuottoja. He havaitsivat, että aiemmilla häviäjillä oli taipumus tuottaa markkinoita paremmin seuraavina vuosina. Tätä ilmiötä selitetään nykyään keskiarvohakuisuudella ja sillä on ollut suuri vaikutus siihen, mitä ajattelemme osakekurssien käyttäytymisestä. Tämän tutkimuksen tavoitteena on selvittää, ovatko Suomen osakemarkkinat (OMXHPI-indeksi) keskiarvohakuisia, ja jos ovat, kuinka kauan kestää, että osakkeiden tuotot palautuvat keskiarvoonsa (50 päivän liukuva keskiarvo), sekä miten keskiarvohakuisuus vaikuttaa riskiin. Keskiarvohakuisuuden esiintymistä tutkitaan käyttämällä muunneltua versiota Lo ja MacKinlayn (1988) varianssisuhteesta sekä Hurstin eksponentista ja puoliintumisajasta. Riskimittareiksi valittiin value at risk ja odotettu alijäämä, joka tunnetaan myös nimellä ehdollinen value at risk. Tulokset osoittavat, että Suomen osakemarkkinat ovat keskiarvohakuisia ja kestää 8–15 kaupankäyntipäivää ennen kuin osakekurssien muutokset palautuvat keskiarvoonsa. Hurstin eksponentilla ja puoliintumisajalla on matala positiivinen korrelaatio riskimittareiden kanssa. Lisäksi ne ovat tilastollisesti merkitseviä selittäjiä riskimittareiden muutoksille robustin keskivirhetestin perusteella. Kun keskiarvohakuisuus voimistuu, myös riskin määrä markkinoilla kasvaa. Puoliintumisajan muutoksilla oli voimakkaampi vaikutus riskiin. Tämän tutkielman tulokset voivat olla arvokkaita salkunhoitajille, jotka pyrkivät suojautumaan riskeiltä tai lisätuottoa hakeville opportunistisille sijoittajille.
Keywords: mean reversion, value at risk, expected shortfall, variance ratio, Hurst exponent, half-life, risk management